PRODUKSI TANAMAN KARET (Hevea brasiliensis) PADA WAKTU PENGUMPULAN LATEKS YANG BERBEDA - Mochlisin Andriyanto; Andi Wijaya; Junaidi .; Arief Rachmawan (Jurnal Agro Estate, 2019)
Latex is a colloidal suspended of rubber particle in rubber tree (Hevea brasiliensis). Technically, the capacity of rubber productivity can be determined by latex collectionperiod after being tapped. The objective of research was to obtain the differences of latex collection period. The study was conducted in September-November 2017 at the Sungei Putih Research Center in Experimental Estate with PB 260 (7 years tapped) on BO-2 (S/2 d3.ET2.5% Ga1.0 6/y(m)).The experimental designused a Randomized Block Design (RBD) with four treatments of latex collection periodi.e 20, 40, 60, 80 minutes after being tapped with three replicates respectively. The parameters observed was gram/tree/tapping (g/p/s), kg/ha/years, latex flow rate (ml/minutes) and total solid content (%).The results showed that latex collection period was significantly different to g/p/s, kg/ha/years and latex flow rate. Total solid content (TSC) was not significantlydifferent in all treatments. The latex collection period of 20 minutes after being tapped had higher productivity than 40, 60, 80 minutes.